2012
DOI: 10.4103/2231-4040.97286
|View full text |Cite
|
Sign up to set email alerts
|

Effect of permeation enhancers on the penetration mechanism of transfersomal gel of ketoconazole

Abstract: The aim of the present research work was to investigate the potential of transfersome formulations for transdermal delivery of Ketoconazole (KTZ). KTZ is a broad-spectrum antifungal agent that is active against a wide variety of fungi and yeasts. It is readily but incompletely absorbed after oral dosing and is highly variable. The transfersomes were formulated by lipid film hydration technique using Rotary vacuum Evaporator. The prepared transfersomes were converted into suitable gel formulation and is evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(17 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…These skin pieces were immersed in normal saline briefly and then mounted between donor and receptor compartments of Franz diffusion cells. The study conditions and analytical methods were identical to in vitro release study as mentioned before (Rajan and Vasudevan, 2012). All experimental procedures including handling, were approved by the Institutional Animal Ethics Committee (Registration number: 144/2013) complied with the guidelines set out by the Committee for the Purpose of Control and Supervision of Experiments on Animals (CPCSEA), Animal Welfare Division, Ministry of Environment and Forests, Government of India, India.…”
Section: Methodsmentioning
confidence: 99%
“…These skin pieces were immersed in normal saline briefly and then mounted between donor and receptor compartments of Franz diffusion cells. The study conditions and analytical methods were identical to in vitro release study as mentioned before (Rajan and Vasudevan, 2012). All experimental procedures including handling, were approved by the Institutional Animal Ethics Committee (Registration number: 144/2013) complied with the guidelines set out by the Committee for the Purpose of Control and Supervision of Experiments on Animals (CPCSEA), Animal Welfare Division, Ministry of Environment and Forests, Government of India, India.…”
Section: Methodsmentioning
confidence: 99%
“…1ml sample was withdrawn at predetermined time intervals for 24 hours and drug content was analyzed by UV-VIS double beam spectrophotometer (ChemitoSpectrascan UV2600, India) at 245nm. [12]…”
Section: Methodsmentioning
confidence: 99%
“…Peppermint oil fragrance, which according to literature (12), may be also used as permeation enhancer, was used as an additive in our gel formulations at diff erent concentrations (0.1, 0.5, 1.0 and 1.5 %, Table II). The results showed that peppermint oil, at concentrations of 0.1, 0.5, and 1.0 % slightly reduced viscosity in all the studied gel samples, whereas at a concentration of 1.5 %, it signifi cantly reduced viscosity in polyacrylic acid polymer-based gels with Ultrez 10, Ultrez 20, and Carbopol 980 but not with Carbopol 940.…”
Section: Resultsmentioning
confidence: 99%